2017
DOI: 10.1002/jbmr.3124
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Using Lumbar Spine Trabecular Bone Score to Adjust Fracture Probability: The Manitoba BMD Cohort

Abstract: Decreased lumbar spine trabecular bone score (TBS), a dual-energy X-ray absorptiometry (DXA)-derived image texture measurement, is a risk factor for major osteoporotic fracture (MOF) and hip fracture (HF) independent of 10-year fracture probability estimated using FRAX. We determined how often applying the TBS adjustment to fracture probability altered treatment qualification. Using a population-based registry containing all clinical DXA results for Manitoba, Canada, we identified 34,316 women with baseline sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 34 publications
3
25
0
2
Order By: Relevance
“…This is in line with some other publications that investigated the relationship between FRAX and TBS . For example, per‐SD increase in FRAX was found to have a HR rising from 1.70 to 1.76 after adjusting for TBS and adding TBS to FRAX yielded a small but significant improvement in overall NRI ranging from 0.7% to 1.8% when compared with FRAX alone . However, another study revealed that although TBS was significantly associated with MOF risk independent of FRAX, there was no significant improvement of discrimination between FRAX adjusted for TBS and FRAX alone .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with some other publications that investigated the relationship between FRAX and TBS . For example, per‐SD increase in FRAX was found to have a HR rising from 1.70 to 1.76 after adjusting for TBS and adding TBS to FRAX yielded a small but significant improvement in overall NRI ranging from 0.7% to 1.8% when compared with FRAX alone . However, another study revealed that although TBS was significantly associated with MOF risk independent of FRAX, there was no significant improvement of discrimination between FRAX adjusted for TBS and FRAX alone .…”
Section: Discussionsupporting
confidence: 89%
“…Findings from observational studies have shown that TBS as a risk‐assessment tool is significantly related to risks of osteoporotic fractures independently of BMD and age . Results from some studies also reported FRAX (Fracture Risk Assessment Tool) in combination with TBS could improve its predictive accuracy for fracture risk, although the improvement was small or nonsignificant …”
Section: Introductionmentioning
confidence: 99%
“…Limitations of this study include lack of information about other potential risk factors, including bone microarchitecture (eg, cortical porosity), trabecular bone score, hip axis length, vertebral imaging, bone turnover marker levels, and objective measures of physical function. In previous studies, two DXA‐derived measures (hip axis length and the trabecular bone score adjustment to FRAX) each provided improvement in net reclassification compared with the FRAX model alone. A study of Japanese women aged ≥40 years showed improvement in risk reclassification for the FRAX with trabecular bone score compared with the FRAX model alone .…”
Section: Discussionmentioning
confidence: 95%
“…Among the clinically applicable techniques developed for bone quality assessment, trabecular bone score (TBS) has been the most extensively studied . TBS can help enhance fracture prediction when used in conjunction with FRAX probability estimated with BMD . TBS measurements were performed in the Bone Disease Unit at the University of Lausanne, Switzerland (TBS iNsight Software, Version 2.1, Med‐Imaps, Merignac, France), using anonymized spine DXA files to ensure blinding of the Swiss investigators to all clinical parameters and outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…(21,22) TBS can help enhance fracture prediction when used in conjunction with FRAX probability estimated with BMD. (23) TBS measurements were performed in the Bone Disease Unit at the University of Lausanne, Switzerland (TBS iNsight Software, Version 2.1, Med-Imaps, Merignac, France), using anonymized spine DXA files to ensure blinding of the Swiss investigators to all clinical parameters and outcomes. We excluded women with BMI outside the range of 15 to 37 kg/m2 as recommended by the TBS manufacturer.…”
Section: Study Populationmentioning
confidence: 99%